Dietrich Bonhoeffer life and legacy - Buchholz, Dana (LIT-Verlag, 2019)
This volume is the documentation of a workshop at the "Dietrich Bonhoeffer Centre for Public Theology" in Kigali, that took place in February 2018 and discussed what can be gained from Bonhoeffer's theology for contextual theologies in Africa as well as in Europe. The core feature of the workshop in February 2018 was a competition in which students from Butare/Huye presented the findings of their examination of Dietrich Bonhoeffer's life and work. The prize-winning contributions are documented in this volume. Papers from the European perspective were contributed by doctoral candidates and students of the Ruhr University Bochum, and the chairing and commentary of the event was shared amongst Dr Clemens Wustmans (Berlin), Dr Christine Schliesser (Bern), the President of the Presbyterian Church in Rwanda, Dr Pascal Bataringaya (Kigali), the Dean of the Theological Faculty of the Protestant Institut of Arts and Social Sciences, Olivier Munyansanga, Ph.D. (Huye/Rwanda), and Prof. Dr Traugott Jähnichen (Bochum)
Keywords: Bonhoeffer, Dietrich -- 1906-1945; Konferenzschrift -- 2018 -- Kigali, Rwanda